Short-term outcomes of robotic versus open pancreatoduodenectomy: propensity score-matched analysis - Nickel, Felix; Wise, Philipp; Müller, Philip C.; Kuemmerli, Christoph; Cizmic, Amila; Salg, Gabriel Alexander; Wagner, Verena; Nießen, Anna; Mayer, Philipp; Mehrabi, Arianeb; Loos, Martin; Müller, Beat P.; et al. (Annals of surgery, 2024)
Objective: The goal of the current study was to investigate the perioperative outcomes of robotic pancreaticoduodenectomy (RPD) and open pancreaticoduodenectomy (OPD) in a high-volume center. - Background: Despite RPDs prospective advantages over OPD, current evidence comparing the 2 has been limited and has prompted further investigation. The aim of this study was to compare both approaches while including the learning curve phase for RPD. - Methods: A 1:1 propensity score-matched analysis of a prospective database of RPD with OPD (2017-2022) at a high-volume center was performed. The main outcomes were overall- and pancreas-specific complications. - Results: Of 375 patients who underwent PD (OPD n=276; RPD n=99), 180 were included in propensity score-matched analysis (90 per group). RPD was associated with less blood loss [500 (300-800) vs 750 (400-1000) mL; P=0.006] and more patients without a complication (50% vs 19%; P<0.001). Operative time was longer [453 (408-529) vs 306 (247-362) min; P<0.001]; in patients with ductal adenocarcinoma, fewer lymph nodes were harvested [24 (18-27) vs 33 (27-39); P<0.001] with RPD versus OPD. There were no significant differences for major complications (38% vs 47%; P=0.291), reoperation rate (14% vs 10%; P=0.495), postoperative pancreatic fistula (21% vs 23%; P=0.858), and patients with the textbook outcome (62% vs 55%; P=0.452). - Conclusions: Including the learning phase, RPD can be safely implemented in high-volume settings and shows potential for improved perioperative outcomes versus OPD. Pancreas-specific morbidity was unaffected by the robotic approach. Randomized trials with specifically trained pancreatic surgeons and expanded indications for the robotic approach are needed.